Systemic gene delivery following intravenous administration of AAV9 to fetal and neonatal mice and late‐gestation nonhuman primates. Issue 9 (10th June 2015) - Mattar, Citra N.; Wong, Andrew M. S.; Hoefer, Klemens; Alonso‐Ferrero, Maria E.; Buckley, Suzanne M. K.; Howe, Steven J.; Cooper, Jonathan D.; Waddington, Simon N.; Chan, Jerry K. Y.; Rahim, Ahad A.
ABSTRACT: Several acute monogenic diseases affect multiple body systems, causing death in childhood. The development of novel therapies for such conditions is challenging. However, improvements in gene delivery technology mean that gene therapy has the potential to treat such disorders. We evaluated the ability of the AAV9 vector to mediate systemic gene delivery after intravenous administration to perinatal mice and late‐gestation non‐human primates (NHPs). Titer‐matched single‐stranded (ss) and self‐complementary (sc) AAV9 carrying the green fluorescent protein (GFP) reporter gene were intravenously administered to fetal and neonatal mice, with non‐injected age‐matched mice used as the control. Extensive GFP expression was observed in organs throughout the body, with the epithelial and muscle cells being particularly well transduced. ssAAV9 carrying the WPRE sequence mediated significantly more gene expression than its sc counterpart, which lacked the woodchuck hepatitis virus posttranscriptional regulatory element (WPRE) sequence. To examine a realistic scale‐up to larger models or potentially patients for such an approach, AAV9 was intravenously administered to late‐gestation NHPs by using a clinically relevant protocol. Widespread systemic gene expression was measured throughout the body, with cellular tropisms similar to those observed in the mouse studies and no observable adverse events. This study confirms that AAV9 can safely mediate systemic gene delivery in small and large animal models and supports its potential use in clinical systemic gene therapy protocols.—Mattar, C. N., Wong, A. M. S., Hoefer, K., Alonso‐Ferrero, M. E., Buckley, S. M. K., Howe, S. J., Cooper, J. D., Waddington, S. N., Chan, J. K. Y., Rahim, A. A. Systemic gene delivery following intravenous administration of AAV9 to fetal and neonatal mice and late‐gestation nonhuman primates. FASEB J. 29, 3876‐3888 (2015). www.fasebj.org